Analisis Dampak Perubahan Iklim terhadap Ekosistem Pesisir dan Pulau Kecil: Studi Kasus Pulau Tanakeke Takalar - Ridwan, Saptariani Putri (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
Climate change is a global challenge affecting the sustainability of coastal and small island ecosystems. Tanakeke Island in Takalar Regency, South Sulawesi, is an area vulnerable to the impacts of climate change, such as sea level rise, coastal erosion, mangrove ecosystem degradation, and declining fisheries yields. This study aims to analyze the impacts of climate change on the coastal ecosystem of Tanakeke Island using qualitative and quantitative descriptive approaches. Data were obtained through field observations, biophysical condition measurements, community interviews, and literature studies. The results indicate significant damage to mangrove forests, increased coastal erosion of up to 2 meters per year, and a decline in marine biodiversity. Local communities are experiencing impacts in the form of reduced fish catches and increased socioeconomic vulnerability. In conclusion, Tanakeke Island requires ecosystem-based adaptation strategies and strengthening community capacity to cope with climate change.